Management of Calcified Coronary Lesions - Khaled Al-Shaibi; Aditya Bharadwaj; Atul Mathur; Ashish Jaikishen; Robert Riley (US Cardiology Review)
With an aging population, coronary calcification is increasingly encountered in modern day interventional practice. Unfortunately, it is associated with lower procedural success and higher rates of periprocedural complications, such as failure to deliver stents, perforations, dissections, and other major adverse cardiac events. Furthermore, suboptimal stent deployment in the setting of severe calcification is associated with both short- and long-term major adverse cardiac events, including stent thrombosis, MI, in-stent restenosis, and target lesion revascularization. A variety of treatment options for these lesions exist, including specialized balloons, atherectomy, and intravascular lithotripsy. While there is currently no universally accepted algorithm for choosing between these treatment strategies, several different algorithms exist, and the optimization of these treatment regimens will continue to evolve in the coming years. This review aims to provide insights on the different therapeutic modalities and an understanding of the current body of evidence.